The Effectiveness of Group Counseling Model through The Behavioral Rehearsal Approach to Overcome Student Social Anxiety - Muhammad Ilham Bakhtiar; Rahmatia Rahmatia (STKIP Singkawang, 2018)
This study aims to find out: (1) the development of group counseling models through the approach Behavioral Rehearsal to overcome Student social anxiety, (2) To find out whether the group counseling model through the approach is Behavioral Rehearsal effective for dealing with students' social anxiety. The method used in the research is Research and development (R & D). The target of this research is the students of Pangkajene 2 State High School in Pangkep Regency. The targeted output of this study is that this study produced a group counseling model Behavioral Rehearsal to overcome students 'social anxiety and effectiveness in overcoming students' social anxiety. This model is the result of the need in the Pangkajene Superior 2 State High School which will later be used as the basis for the development of protype to help students overcome social anxiety problems. Then the results of the prototype will be a draft guide and published in the seminar forum in the form of proceedings. The results of the draft from protype development were then validated by experts (expert guidance and counseling and psychology) and practitioners as users of this group's counseling model. In addition, this year also will test the effectiveness of the product on the group's product or model of counseling to students. Research results will be published in nationally accredited scientific journals and published through proceedings through national seminars. The results of the study were (1) the school experienced problems related to research studies, then the condition of the school that was maximal applied group counseling especially using approaches and in school there were various problems of social anxiety then group counseling activities were carried out with five sessions. (2) The results of the expert validation test stated that this guide was suitable to be used (3) the results of the percentage analysis explained that there was a decrease in value after the group counseling activities with a behavioral rehearsal approach.